2022
DOI: 10.1177/09567976211056623
|View full text |Cite
|
Sign up to set email alerts
|

Are You for Real? Perceptions of Authenticity Are Systematically Biased and Not Accurate

Abstract: Can people accurately perceive who is authentic? Laypeople believe they can tell who is authentic, and they report that authenticity is an important attribute in others (Studies 1a and 1b; N = 369). However, when we directly tested the accuracy of perceived authenticity, we found no significant correlation between self- and other-rated authenticity in two cohorts of adult students in randomly assigned teams (Studies 2 and 3; 4,040 self-other observations). In addition, we found that perceived authenticity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Our perspective also helps explain questions raised by the recent empirical findings of Bailey and Levy (2022). Perhaps surprisingly, the authors found that there was a negligible correlation between self- and other-rated authenticity on randomly assigned teams.…”
Section: Authenticitymentioning
confidence: 51%
See 3 more Smart Citations
“…Our perspective also helps explain questions raised by the recent empirical findings of Bailey and Levy (2022). Perhaps surprisingly, the authors found that there was a negligible correlation between self- and other-rated authenticity on randomly assigned teams.…”
Section: Authenticitymentioning
confidence: 51%
“…Past research has found that self- and other-rated authenticity tend to diverge from one another (Bailey & Levy, 2022). We find one reason why self- and other-rated authenticity diverge: While positivity is a sign of authenticity to the self, it is a sign of in authenticity to others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, both mechanisms mediated the effects for committed, embedded and moral attitudes. This integrates hypocrisy research with a broader literature on perceived authenticity (Bailey & Levy, 2022;Kernis & Goldman, 2006;Newman, 2019;Sutton, 2020) in which inaccurate self-knowledge prompts disliking (Garcia, 2019;Liu & Perrewe, 2006).…”
Section: Discussionmentioning
confidence: 96%